Raising Public Awareness About Flood Danger In Tanjung Agung Village, Bengkulu City - Henni Febriawati; Riska Yanuarti; Oktarianita Oktarianita (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Natural disasters are still a concern and problem in the world, including in Indonesia. Indonesia is a country that is prone to flooding, so it is very risky to cause material losses that can cost many lives. Tanjung Agung Village is one of the areas in Bengkulu City which continues to be flooded every year, even the frequency of flooding can be two to three times a year with inundation heights reaching one and a half meters from the ground. This community service is carried out for the residents of RT. 03 Tanjung Agung Village, Bengkulu City with activities including health education on preparedness to face flood disasters, simulation of flooding, mutual cooperation and tree planting. The results of the activity show that the community' s desire to start caring for the environment can be seen from the enthusiasm of the community in every series of activities ranging from health education, simulation, mutual cooperation and tree planting as an effort to minimize the risk of flood disasters during heavy rains. It can be concluded that this activity has a positive impact on supporting and increasing knowledge and increasing awareness of the RT community. 03 Tanjung Agung Village, Bengkulu City regarding the danger of flooding.